STUDI PERENCANAAN PERKERETAAPIAN DI PROVINSI SULAWESI SELATAN - AS, Nur Syam (Teknosains, 2013)
The train is an alternative transportation mode provides both passenger and freight service because it has a large carrying capacity in units of the number of passengers or freight (ton), the use of energy-efficient, environmentally friendly as well as the needs of small land. This activity is intended to formulate policy and plan development of rail transport are integrated region in accordance with the pattern of traffic movement and Spatial Planning of South Sulawesi province. While the aim to determine the pattern of regional transportation road user movement, anticipating a high demand for transport services and thus require greater capacity, and the existence of alternative modes of transportation can be a good option for people to transport passengers and goods.Stats railways of South Sulawesi province region produces 3 corridors that cross the West, Central Crossing and East Cross. 3. Construction of the rail network in South Sulawesi region requires a very large cost, so the realization priority corridor segments Mamminasata and West Cross-Makassar Makassar-Pare-Pare and Bulukumba. Priority of railway construction is Mamminasata area as the first priority, Cross-Makassar-Pare-Pare second priority and third priority Makassar-Bulukumba.Keywords: Railway, West Cross, and the Middle East.